Liquid Chromatographic Method for the Quantification of Antipsychotic Agent Iloperidone in Pharmaceutical Formulation. (14th March 2012) - Chhalotiya, Usmangani K.; Bhatt, Kashyap K.; Shah, Dimal A.; Patel, Jigar R.
Abstract : Liquid chromatographic method for the quantitative determination of iloperidone in the pharmaceutical dosage form was developed. A reversed phase column with mobile phase containing 0.02 M potassium dihydrogen phosphate: methanol: acetonitrile (55 : 25 : 20, v/v/v, pH 4 adjusted with phosphoric acid) was used. The flow rate was 1.0 mL min −1, and effluents were monitored at 230 nm. The retention time of iloperidone was 11.6 min. Iloperidone stock solutions were subjected to acid and alkali hydrolysis, chemical oxidation, and dry heat degradation. The degraded product peaks were well resolved from the pure drug peak with significant difference in their retention time values. Stressed samples were assayed using developed LC method. The proposed method was validated with respect to linearity, accuracy, precision, and robustness. The method was successfully applied to the estimation of iloperidone in tablet dosage forms.